Bilateral radial collateral ligament rupture in a shoemaker: A case report and brief literature review. Issue 19 (May 2020) - Li, Yueying; Wu, Guangzhi; Cui, Shusen; Zhang, Zhan; Gu, Xiaosong
Abstract: Introduction: Rupture of the radial collateral ligament (RCL) of the index metacarpophalangeal (MCP) joint is mostly related to acute local mechanical causes, which severely affect the stability of the MCP joint. However, few cases of chronic bilateral job-related RCL injury have been reported in the literature. There is no consensus on the knowledge of the disease to date. Here, we present an extremely rare case of chronic bilateral RCL injury. Patient concerns: A 58-year-old female shoemaker presented with chief complaints of swelling and pain in the radial aspect of the MCP joint of bilateral index fingers since 2 years. There was no history of acute RCL injury. The persistent pain was aggravated while gripping, pulling, buttoning, and twisting. Diagnosis: Based on the combination of physical examination, X-ray, and ultrasonic and magnetic resonance imaging, the patient was diagnosed with bilateral tear of the RCLs and joint dislocation of the index MCP joint. Eventually, intra-operative findings confirmed the diagnosis. Intervention: The patient underwent bilateral index MCP joint fusion followed by immobilization for 6 weeks. Functional therapy was started after immobilization. Outcomes: The patient's chief complaints were significantly alleviated after the operation. At the 12-month follow-up, the patient returned to a full level of activity as a shoemaker without any complications. Conclusion: Compared to acute RCL rupture of the index MCP joint, occupation may play an important role in the diagnosis of chronic RCL rupture of the index MCP joint. Our report will provide more diagnostic and treatment experience to deal with this type of injury.